Assessing historical thinking skills in high school history education: a Padlet-based approach - Ofianto, Ofianto; Rahmi, Ulfia; Syafrini, Delmira; Ningsih, Tri Zahra (Journal of Education and Learning (EduLearn), 2024)
This research is focused on assessing how the incorporation of Padlet technology affects the evaluation of historical thinking skills in high school history education. The research methodology involved a pretest-posttest approach with a randomly selected group of 70 students. The research tool employed questionnaires aligned with the study’s objectives. Data analysis utilized comparative statistics, specifically the paired sample t-test. The outcomes of the study reveal a significant positive impact resulting from the integration of Padlet technology in assessing historical thinking skills. This is substantiated by the sign value being less than 0.05 for all aspects examined. Consequently, this research provides compelling evidence that this approach can serve as an effective alternative for improving the quality of history education at the high school level. The findings of this study have important implications for educators, learners, and other stakeholders. These results may be used by educators to create more successful teaching strategies that will improve their students' historical thinking and comprehension. As a personal learning tool, Padlet technology can help students comprehend the historical subjects they are studying better. For those involved, this study offers compelling proof that using Padlet technology in high school history curricula may improve its caliber.